The Role of Twitter in Disaster Communication by the Indonesian Government: A Case Study of the Cianjur Earthquake - Gusti Naufal Rizky Perdana (Metacommunication: Journal of Communication Studies, 2025)
Indonesia is a country highly prone to natural disasters, including earthquakes. In this context, social media—particularly Twitter—plays a crucial role in facilitating disaster communication between the government and the public. This study aims to analyze how two Indonesian government agencies, the Meteorology, Climatology, and Geophysics Agency (BMKG) and the National Disaster Management Agency (BNPB), utilized Twitter to disseminate disaster-related information following the Cianjur earthquake in November 2022. A qualitative content analysis method was applied to examine the official Twitter accounts @InfoBMKG and @BNPB_Indonesia, using NVivo 12 Plus software. The findings reveal that @InfoBMKG demonstrated higher communication intensity and a stronger focus on earthquake-related issues, both in terms of tweet volume and the use of relevant hashtags, compared to the more general content shared by @BNPB_Indonesia. This study concludes that the frequency, consistency, and relevance of shared content significantly influence the effectiveness of government disaster communication on social media. These insights are expected to contribute to the improvement of risk communication strategies and disaster information management in Indonesia.